Laboratory investigation of adult small ruminant Leptospirosis, a neglected infection in Greece: problems and recommendations - BISIAS (Α.Γ. ΜΠΙΣΙΑΣ), A. G.; KRITAS (Κ.Σ. ΚΡΗΤΑΣ), C. S.; BILLINIS (Χ. ΜΠΙΛΛΙΝΗΣ), C. H.; BURRIEL, R. A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Leptospirosis is in Greece a neglected infection. Small ruminants and specifically sheep are accidental hosts of Leptospira spp, but they could also be disseminators of pathogenic serovars. Thus, the objective was to investigate leptospirosis of adult small ruminants coming from areas in Southern Greece, where accidental evidence had showed that leptospirosis could be an important infection for man and animals. For this purpose, blood and kidney samples were collected at slaughter from adult females. Collected samples were examined with a commercial serological screening kit, the microagglutination test ( MAT), histology and PCR. One hundred ten serum and 110 tissue samples were collected. Of the examined serum samples 55 (50%) were suspect for leptospirosis in the screening kit and 28 (25.45%) were MAT positive. Of the tissue samples 38 (34.5%) were PCR positive and 30 (27.2%) showed various degrees of microscopic kidney lesions. The serovars identified by the MAT were Tarassovi (10 animals), Autumnalis (8 animals), Zanoni (4 animals), Hebdomadis and Javanica (2 each), Bratislava and Hardjio prajitno (one each). The conclusion is that small ruminants and specifically sheep (98 animals) are disseminators of pathogenic Leptospira spp. serovars in areas where they predominate and climatic factors favor the survival of the pathogen.